1994
DOI: 10.1523/jneurosci.14-06-03643.1994
|View full text |Cite
|
Sign up to set email alerts
|

c-fos expression in vomeronasal pathways of mated or pheromone- stimulated male golden hamsters: contributions from vomeronasal sensory input and expression related to mating performance

Abstract: The vomeronasal system projects to the accessory olfactory bulb (AOB), to the medial (Me) and posterior medial cortical nuclei (PMCN) of the amygdala, to the bed nucleus of the stria terminalis (BNST), and to other central structures shown to be important in mating behavior, including the medial preoptic area (MPOA). In these experiments c-fos expression was used as a marker of neural activity to identify the contribution of vomeronasal sensory input during mating behavior in male golden hamsters, either intac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(104 citation statements)
references
References 40 publications
9
94
0
1
Order By: Relevance
“…These ejaculation-related Fos-IR neurons were situated in the lateral part of the MEApd, separately from the Fos-IR neurons observed following intromissions. This characteristic pattern has also been described by other investigators in rats [2] and is similar to the pattern observed in male hamsters, where two clusters of cells appear following mating including ejaculation in the lateral part of the MEApd [11,18,48].…”
Section: Ejaculation-related Clusters Of Fos-ir Neuronssupporting
confidence: 88%
See 2 more Smart Citations
“…These ejaculation-related Fos-IR neurons were situated in the lateral part of the MEApd, separately from the Fos-IR neurons observed following intromissions. This characteristic pattern has also been described by other investigators in rats [2] and is similar to the pattern observed in male hamsters, where two clusters of cells appear following mating including ejaculation in the lateral part of the MEApd [11,18,48].…”
Section: Ejaculation-related Clusters Of Fos-ir Neuronssupporting
confidence: 88%
“…One cluster was situated in the rostral extension of the BNSTpm close to the ventricle. This cluster was also observed in male hamsters following mating including ejaculations [11]. In male rats we ob served an additional cluster of Fos positive cells in the caudal aspect of the BNSTpm, in a subregion situated close to the fornix, following ejaculation.…”
Section: Ejaculation-related Clusters Of Fos-ir Neuronsmentioning
confidence: 64%
See 1 more Smart Citation
“…This effect of olfactory deprivation on sexual behavior may be mediated by GnRH neurons. Indeed, as mentioned previously, GnRH cells receive olfactory information from both the main and the accessory olfactory system and an icv injection with GnRH is able to overcome the absence of olfactory inputs in a way similar to that of sexual experience [29,30,77,79]. Therefore, it is possible that sexual experience modulates the relative functional efficiency of these MOB to GnRH neuron connections; these connections gaining functional efficiency only after sexual experience.…”
Section: Olfactory Control Of Sexual Behaviormentioning
confidence: 89%
“…These two sensory organs have their own distinct primary projection targets, connecting to the main olfactory bulb (MOB) and the accessory olfactory bulb (AOB) respectively, which each then connect to different forebrain nuclei comprising the main olfactory system and the vomeronasal system [11]. The MOB sends projections to secondary processing areas including the piriform cortex, the anterior olfactory nucleus and the cortical amygdala, while the AOB has bidirectional connections with the medial amygdala and the bed nucleus of stria terminalis with further output to the ventral hypothalamus [28]. While the two systems converge at the level of the amygdala [82], the segregation of the two systems and the extensive functional differences between them have given rise to the traditional view that the MOE detects volatile odorants in the environment while the VNO detects non-volatile pheromones [14].…”
Section: Pheromone Detectionmentioning
confidence: 99%